Pleurabrade: A Spiral Brush for Mechanical Pleurodesis and a Review of the Literature - Young, John S.; Steimer, Desiree A.; Polhemus, Emily; Bueno, Raphael (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Background While the optimal treatment for primary spontaneous pneumothorax remains unclear, mechanical pleurodesis is a well-established treatment. The Pleurabrade is a spiral brush designed for mechanical pleurodesis during thoracoscopy. We present two patients who underwent mechanical pleurodesis with the Pleurabrade.Case Description Two patients with spontaneous pneumothorax underwent operative intervention including mechanical pleurodesis with the Pleurabrade. Chest tubes were removed within 48 hours postoperatively and they were discharged home. Both patients remain recurrence free at 11 and 22 months, respectively.Conclusion While further testing is needed, these case reports and operative video highlight the Pleurabrade as an efficient device for thoracoscopic mechanical pleurodesis.
Keywords: mechanical pleurodesis; spontaneous pneumothorax; pleural abrasion